Implementasi Pembentukan Kader Kesehatan Dalam Menunjang Pelayanan Kesehatan Bagi WBP di Rumah Tahanan Negara Kelas IIB Balige - M.N. Patricia Simanjuntak; Ali Muhammad (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The most basic right for WBP is to receive adequate health services. Various health efforts are carried out through prevention, healing and improving health services at the Balige Class IIB Detention Center. In order to overcome obstacles related to health services in detention centers, a WBP health cadre was formed at the Balige Class IIB Detention Center. The aim is to overcome the problems of handling and reporting the health of WBPs to improve health services for WBPs themselves. This research was carried out using a qualitative approach with descriptive methods. Data collection techniques were carried out through observations carried out during KKN, as well as secondary data carried out using documentation studies and field recording. From the research results, it is known that the program to form health cadres for inaan residents at the Balige Class IIB Detention Center has shown positive results. The implementation of this program has succeeded in improving the quality and accessibility of health services at the Class IIB Balige Detention Center.